The influence of maternal disease on metabolites measured as part of newborn screening - Ryckman, Kelli K (2013)
OBJECTIVE: Measurements of neonatal metabolites are commonly used in newborn screening programs to detect inborn errors of metabolism. Variation in these metabolites, particularly in infants born preterm (<37 weeks gestation), can result from multiple etiologies. We sought to evaluate the impact of maternal complications of pregnancy and environmental stressors on newborn screening metabolites. METHODS: We examined 49 metabolic biomarkers obtained from routine newborn screening in 452 infants born preterm for association with maternal environmental stressors and complications of pregnancy. RESULTS: Neonatal free carnitine (C0, P=1.4×10(−7)), acetylcarnitine (C2, P=2.7×10(−7)), octenotylcarnitine (C8:1, P=5.2×10(−11)) and linoleoylcarnitine (C18:2, P=9.1×10(−7)) were elevated in infants born to preeclamptic mothers. Similar elevations were observed in small for gestational age infants and in infants where labor was not initiated prior to delivery. When accounting for all three factors associations remained strongest between acylcarnitines and preeclampsia. CONCLUSION: We observed that maternal conditions, particularly preeclampsia, influence newborn screening biomarkers. This is important for identifying maternal conditions that influence metabolites measured during routine newborn screening that are also markers of fetal growth and overall health.